Fluid simulation for computer graphics - Bridson, Robert 1976- (CRC Press, Taylor & Francis Group, 2016)
"A practical introduction, the second edition of Fluid Simulation for Computer Graphics shows you how to animate fully three-dimensional incompressible flow. It covers all the aspects of fluid simulation, from the mathematics and algorithms to implementation, while making revisions and updates to reflect changes in the field since the first edition."--Cover.